Levon-Zaven Surmelian – Armenian Poet, American English – Language Novelist - Muradyan, Arpi (Bulletin of Yerevan University B: Philology, 2026)
The Armenian writer Levon-Zaven Surmelian (1905-1995), who wrote in a foreign language, lost his parents and relatives during the Armenian Genocide and passed through a life path full of trials.The author of the article, having studied the life and literary heritage of L.-Z. Surmelian on the background of the events of his time and having compared the materials and facts concerning L.-Z. Surmelian published in the press and various collections, supplemented and clarified some episodes of the author's biography. The article focuses on the correspondence between L.-Z. Surmelian and Arshak Chopanian.The article describes how a promising Armenian poet, who became famous thanks to his collection “Luys Zvart” (“Life-Giving Light”) (1924), has made a “language transition” from Armenian to English in the American environment through his hard work, has become a well-known specialist in the field of English language and English-language literature, and has worked for a long time in the American universities, using his book “Technique of Fiction – Measure and Its Absence” as a teaching  manual for students.This fact-filled article has presented the process of the transformation of the Armenian poet into an English-language writer-novelist, as well as the path passed by the author of the poignant autobiographical novels “I Ask You, Ladies and Gentlemen” and “98.6°,” thanks to which he entered the American literature and took an honorable place among the Armenian authors writing in foreign languages.
Keywords: English writer; Tekeyan; biography; Greek; correspondence; tragedy; Trabzon; genocide; Surmelyan; Constantinople; Kansas; Postajyan